2018
DOI: 10.1155/2018/4127031
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Incidence of Seismic Wave Reflecting Two Components of Design Ground Motion

Abstract: The wave field on the artificial boundary was separated into the free field without local topography effect and scattering field induced by local topography effect. The simulation of the free field under obliquely incident waves was conducted. Based on the assumption that the components of design ground motion were treated as the coincidence of oblique P wave and oblique SV wave, the relationship between the oblique input waves and the design ground motion was established in the free field. Further, the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The abovementioned detrimental effects of oblique incidence were also observed in other relevant research. For instance, Cen [32] concluded that the increase of incident angle could lead to larger seismic response of the dam. Gao [5] studied the seismic performance of bridges and concluded that the structure was more fragile when the incident angle of SV waves was 30°.…”
Section: The Influence Of Oblique Incidence Of Sv Waves On the Seismic Fragility Of Structuresmentioning
confidence: 99%
“…The abovementioned detrimental effects of oblique incidence were also observed in other relevant research. For instance, Cen [32] concluded that the increase of incident angle could lead to larger seismic response of the dam. Gao [5] studied the seismic performance of bridges and concluded that the structure was more fragile when the incident angle of SV waves was 30°.…”
Section: The Influence Of Oblique Incidence Of Sv Waves On the Seismic Fragility Of Structuresmentioning
confidence: 99%